2022
DOI: 10.3390/cells11030441
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Post-Transcriptional Regulation of Autophagy

Abstract: Autophagy is a widely conserved process in eukaryotes that is involved in a series of physiological and pathological events, including development, immunity, neurodegenerative disease, and tumorigenesis. It is regulated by nutrient deprivation, energy stress, and other unfavorable conditions through multiple pathways. In general, autophagy is synergistically governed at the RNA and protein levels. The upstream transcription factors trigger or inhibit the expression of autophagy- or lysosome-related genes to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 98 publications
0
28
0
Order By: Relevance
“…To investigate the influence of autophagy on STAT6 integrity, we examined the fate of the transcription factor in condition conducive to induction of autophagy and used either autophagy inducers or blockers. It is interesting that treatment of cells with Torin1, a bonafide inducer of macroautophagy [ 43 ], exerted no additional effect on STAT6 degradation upon AA starvation, while treatment with established inhibitors of macroautophagy, 3-MA or HCQ, did not block degradation of the transcription factor (Fig. 4 G).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the influence of autophagy on STAT6 integrity, we examined the fate of the transcription factor in condition conducive to induction of autophagy and used either autophagy inducers or blockers. It is interesting that treatment of cells with Torin1, a bonafide inducer of macroautophagy [ 43 ], exerted no additional effect on STAT6 degradation upon AA starvation, while treatment with established inhibitors of macroautophagy, 3-MA or HCQ, did not block degradation of the transcription factor (Fig. 4 G).…”
Section: Resultsmentioning
confidence: 99%
“…LncRNA is a transcribed RNA of more than 200 nucleotides in length that is involved in a range of cell biological processes, including transcription initiation ( 27 ), transcriptional regulation ( 28 ) and chromatin modification ( 29 ). In recent years, an accumulating number of studies have indicated that lncRNAs are closely related to the initiation and progression of many kinds of cancers and have been used in the diagnosis and prognostic analysis of various cancers ( 30 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a complex process. Emerging studies have shown that circRNAs can influence disease progression via autophagy regulation, by relying on the transcriptional and post-transcriptional modifications of autophagy-related genes ( 112 ). CircRNAs can regulate autophagy by influencing transcription factors at the RNA level.…”
Section: How Circrnas Influence Disease Progression Through the Regul...mentioning
confidence: 99%